The Public Works Loan Board and the growth of the state in nineteenth‐century England1. (15th December 2017) - Webster, Ian
Abstract: The nineteenth‐century archive of the Public Works Loan Board (PWLB) has been overlooked by economic historians. Yet the archive reveals how the PWLB came to play a major part in the financing of new schools, water supplies and sewers in the 1870s. Ten thousand loan applications have been analysed to highlight the changing patterns of the PWLB's lending, while the 60 volumes of minutes indicate why the pattern changed. The analysis shows that in the 1870s there was a large rise in local infrastructure investment caused by the switch from permissive to compulsory public health and education legislation. At the same time, the PWLB became predominantly a low‐cost, rather than a market rate, lender. This change shows how MPs' views developed as they became more sensitive to the impact of the local costs of parliamentary legislation. Overall, the activities of the PWLB illustrate the legislative and institutional changes that contributed significantly to the growth in the role and spending of the state.